An artificial neural network approach to estimate fault location on transmission lines - 267920 Sathyan Anbalakan; Mohd. Hafiz Habibuddin, supervisor; Fakulti Kejuruteraan Elektrik (2007)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik - Elektrik)) - Universiti Teknologi Malaysia, 2007